Avaliação da motivação do uso de sistemas “partilha de viagem” como forma de transporte alternativo nas cidades de Maputo e Matola - Federhen, Anette Katharina (2021)
The fleet of private cars in Maputo and Matola tends to grow and it causes a number of negative effects like traffic congestion and increased costs for maintenance of infrastructures. Mitigating negative effects involves reducing transport and consequently changing citizens' mobility habits.The main objective of this work is to determine whether real time ride sharing could be applicable in the cities of Maputo and Matola in view of the need to change mobility habits. For this purpose, an affirmative and negative hypothesis was formulated regarding the acceptance of ride sharing systems and studied in Maputo during the year 2016.The research method is exploratory, using interviews, an online survey and a bibliographic study. 111 completeanswers, corresponding to 55% of the collected answers were analyzed through the online statistic application qualtrics.com. As expected, the non-response rate was high and the error reached was 19%. Survey respondents answered 34 questions focused on theperceived value of their current mobility as well as the imaginative value of their mobility using a travel-sharing system in the driver or passenger approach.The conclusion of the work is that the negative hypothesis is rejected, because the factor "Social consciousness and for the environment" stands out affirmatively in multiple approaches by both segments, drivers and passengers. Moreover, there are ambiguous variables that have been evaluated differently by the two segments, namely the time factor, changes in habits and safety.Finally,the paper suggests that survey participants prefer to use closed-ride sharing systems, where they can travel with known people.